CASE REPORT KALLMANN SYNDROME IN A 14-YEAR-OLD BOY - Anggraeni, Melisa; Arimbawa, Made; Suryawan, IW Bikin (Medicina; Vol 44 No 1 (2013): Januari 2013)
Normal 0 false false false IN X-NONE X-NONE Kallmann syndrome is a combination of hypogonadotropic–hypogonadism due to gonadotropine releasing hormone ( GnRH ) deficiency with anosmia or hyposmia. Magnetic resonance imaging (MRI) reveals hypoplasia or aplasia of the olfactory bulbs. The incidence is estimated at 1 in 10.000 and 50.000 males and females respectively. The main clinical features consists of the absence of spontaneous puberty, partial or total loss of the sense of smell (anosmia). In this case report , we describe a 14 year old boy with Kallmann s yndrome who was refferred with delayed puberty and lack of smell function . Physical examination revealed Tanner stage I and proven anosmia from olfactory test. Laboratory test showed low titer of testosteron. Testicular ultrasonography (USG) revealed small testicles. Treatment of this particular patient was with a 25 mg of intramuscular testosterone injection and were then increased by 25 mg every two weeks. Proper management of patients with Kallmann s yndrome usually allows them to attain normal reproductive health. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Kallmann syndrome, hypogonadotropic-hypogonadism, anosmia